Study of Some Demographic Characteristics for Diabetic Nephropathy Patients: Case-Control Study - Mahmood, Yasser Saeed; Jawad, Murtadha M. (Medical Science Journal for Advance Research, 2023)
Background: A case-control study conducted on (90) persons of both sexes and ages participated in the case-control study, including (45) Diabetic nephropathy (DN) patients and (45) healthy people. The patients ranged in age from 30 to 82 years old. Whole blood samples were gathered from DN patients at: the Laboratory of kidney disease center at Al-Sadr Medical City , the Laboratory of kidney disease center Al-Najaf Al-Ashraf Teaching Hospital , the Laboratory of Najaf Center for Dialysis and Hematology, and the kidney disease center Laboratory of Al-Hakeem General Hospital in Najaf Governorate, Iraq during the period from November 2022 to January 2023. All patients with Diabetic nephropathy (DN) were under go hemodialysis and were diagnosed with diabetes. An Individuals in the healthy group had no history or clinical symptoms of diabetes or kidney diseases.